2018
DOI: 10.3390/su10082813
|View full text |Cite
|
Sign up to set email alerts
|

Why the Uncertain Term Occurs in the Farmland Lease Market: Evidence from Rural China

Abstract: Urbanization and aging of the agricultural population lead to the insufficient supply of agricultural labor and land being idle in rural China, calling for the farmland lease market to maintain sustainable and efficient use of farmland. However, rural households tend to agree on an uncertain term for farmland leasing in/out, which leads to low efficiency and land loss in agriculture. Therefore, using the survey data collected from 2704 rural households and a logistic regression model, we examine the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Tax incentives and subsidies aimed at stimulating the leasing of farmland have been identified as an efficient mechanism to make land leasing more attractive to landowners who do not wish to farm the land themselves. A study by [78] has shown that farm subsidies have a positive and significant effect on both farmland leasing-in and leasing-out choices. The study indicated that rural households receiving grain subsidies are more likely to lease out (1.5 per cent) and lease in farmland (3.2 per cent).…”
Section: Tax Incentives and Subsidiesmentioning
confidence: 99%
“…Tax incentives and subsidies aimed at stimulating the leasing of farmland have been identified as an efficient mechanism to make land leasing more attractive to landowners who do not wish to farm the land themselves. A study by [78] has shown that farm subsidies have a positive and significant effect on both farmland leasing-in and leasing-out choices. The study indicated that rural households receiving grain subsidies are more likely to lease out (1.5 per cent) and lease in farmland (3.2 per cent).…”
Section: Tax Incentives and Subsidiesmentioning
confidence: 99%
“…Labor and land input significantly affect the total agricultural output [10]. Appropriate employment of labor and the intensive planting of land can improve agricultural economic benefits [12], while the insufficient labor supply and land loss caused by idle land have a serious negative impact on agricultural economic benefits [13].…”
Section: Introductionmentioning
confidence: 99%